2022
DOI: 10.1111/jcmm.17457
|View full text |Cite
|
Sign up to set email alerts
|

The association between common serum adipokines levels and postmenopausal osteoporosis: A meta‐analysis

Abstract: The clinical relevance of blood levels of adipokines in individuals with postmenopausal osteoporosis (PMOP) has not been previously clarified. We performed this meta‐analysis to clarify the association between three common adipokines levels and the occurrence of PMOP. PubMed, Embase, Cochrane library, and China National Knowledgement Infrastructure (CNKI) were searched for collecting articles published before 31 October 2021, without language and status restrictions. Fourteen studies met the selection criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There was considerable heterogeneity of results in this meta-analysis, which may significantly weaken the validity of the results. However, this meta-analysis had strong points, such as the relationships between three common adipokines with the occurrence of PMOP were investigated, and at the same time, the differences in the levels of adipokines and the relationships of different adipokines with BMD and BMI were estimated, and the quality of the included studies was average ( 13 ). Evidence from another systematic review and meta-analysis showed that leptin had a significant positive association with BMD and BMC in all populations, except in boys, especially in girls and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was considerable heterogeneity of results in this meta-analysis, which may significantly weaken the validity of the results. However, this meta-analysis had strong points, such as the relationships between three common adipokines with the occurrence of PMOP were investigated, and at the same time, the differences in the levels of adipokines and the relationships of different adipokines with BMD and BMI were estimated, and the quality of the included studies was average ( 13 ). Evidence from another systematic review and meta-analysis showed that leptin had a significant positive association with BMD and BMC in all populations, except in boys, especially in girls and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the relationship between serum leptin levels and bone metabolism is complex, no definitive conclusions have been drawn on this issue ( 12 , 13 ). As far as we know studies that have examined both human and animal studies to determine the relationship between leptin serum level and BMD is necessary to reach a more specific result.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout mice lacking chemerin receptors CMKLR1 and GPR1 show reduced bone mass and osteoblast differentiation, indicating that chemerin signaling plays a significant role in regulating bone formation in the body [31]. Adiponectin shows a significant negative correlation with bone density [32]. Adiponectin, with a protein structure, is a hormone synthesized by adipocytes.…”
Section: Changes In Adipokine Levelsmentioning
confidence: 99%
“…Ansari MGA, (2020) nồng độ leptin cho thấy không có mối liên quan đáng kể nào với MĐX [9]. Linyuan S, (2022), không có sự khác biệt về nồng độ leptin với MĐX sau khi loại bỏ ảnh hưởng gây nhiễu [10].…”
Section: Mối Liên Quan Giữa Mđx Với Nồng độ Leptin Huyết Thanhunclassified